Synthesis, X-ray diffraction studies, thermal behavior and catalytic investigation of Cu(II) complexes for levulinic acid-based polyol esters - Hossain, Md Anwar; Low, Cheryl Yi Lian; Sheikh, Chan Miya; Juan, Joon Ching; Lee, Hwei Voon (Elsevier, 2019)
Three new copper(II) complexes [Cu(Phe)(Phen)Cl].H2O (1), [Cu(Tyr)(Phen)Cl].H2O (2) and [Cu(Phe)(Tyr)Cl].H2O (3) (Phe = L-phenylalanine, Tyr = L-tyrosine and Phen = 1,10-phenanthroline) have been synthesized with aromatic amino acids and versatile organic 1,10-phenanthroline as mixed ligands and characterized by elemental analysis, FTIR, magnetic susceptibility, single crystal-XRD, powder-XRD, TGA/DTA and SEM techniques. The structural analysis of the complexes revealed that L-phenylalanine and L-tyrosine was coordinated to Cu(II) ion through amino nitrogen and carboxylate oxygen whereas, 1,10-phenanthroline was coordinated by the two nitrogen atoms. In all the cases, the Cu(II) ion has occupied the centre of the square pyramidal coordination, being equatorially bonded by both amino acids and 1,10-phenanthroline, while axially by chlorine atom. In addition, the thermal analysis (TGA/DTA) indicated the presence of lattice water molecules outside the coordination sphere. The catalytic activity of the synthesized complexes was further investigated via esterification of polyols (e.g., neopentyl glycol, trimethylolpropane and pentaerythritol) with biomass-derived levulinic acid (model acid) under mild reaction conditions. Indeed, the esterification reaction reveals that the Cu(II) complex with L-phenylalanine and 1,10-phenanthroline ligands exhibited a significantly high catalytic activity among them.